Student Integrative Islamic Boarding School Education Management Model - Apriyanto, Nur; Hidayati, Dian (International Journal of Educational Management and Innovation, 2022)
The rapid development of higher education if not balanced with an intense spirituality, will be dangerous. Higher education integrated with pesantren attempts to balance technological progress and spiritual strength. Pesantren integrated with universities as part of the modern world and proved that the pesantren program is no longer considered old and backward. The existence of tertiary institutions that integrate pesantren is a form of public service in responding to various challenges in implementing education in Indonesia in a complete and balanced form between character and cognitive. The research method used to describe the integrity management model of pesantren education for students in Yogyakarta is qualitative descriptive with Data collection techniques in interviews, documentation, and observation. This study shows that: (1) The integration model of universities and pesantren in Yogyakarta is not carried out in one model. (2) Management of Islamic boarding school education carried out by the Tarbiyah Madani School of Science is linear integration management. (3) Educational Management Islamic boarding school conducted by Stikes Surya Global is a non-linear, fully integrated management type. (4) Management of Islamic boarding schools carried out by Unires Universitas Muhammadiyah Yogyakarta is a type of partial integration management (5) In implementing the management of Islamic boarding schools, Students in Yogyakarta are seen using good modern management. (6) Management of islamic boarding school students shows professional and accountable management in all elements.